2020
DOI: 10.1186/s13071-020-04368-9
|View full text |Cite
|
Sign up to set email alerts
|

Variation in hatching responses of Nematodirus battus eggs to temperature experiences

Abstract: Background Nematodirus battus, unlike most other gastrointestinal nematodes, undergoes maturation to an infective larva within the egg. Historically, eggs were considered to require a period of chilling over winter followed by a period of temperature above 10 °C for synchronous hatching to occur (generally in spring). Anecdotal reports of Nematodirus infection out-with spring in veterinary journals and the farming press suggest that the concentrated pasture abundance of N. battus infective larvae may be changi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…10 Changes in the dynamics, life history traits, timing of infection and pathogenicity of helminth infections have been reported in recent years and such variation has been particularly evident in Nematodirus battus, an economically important parasite which threatens lamb health and sheep farming sustainability in the UK. With apparent changes in epidemiology of N. battus and the emergence of BZ-resistance in this species, [11][12][13][14] it provides an interesting case study to explore variation throughout the country. It is important to understand variation in disease observed on farm, current management practices employed and the rationale behind these control strategies to support the development of optimised control practices in the future.…”
Section: Introductionmentioning
confidence: 99%
“…10 Changes in the dynamics, life history traits, timing of infection and pathogenicity of helminth infections have been reported in recent years and such variation has been particularly evident in Nematodirus battus, an economically important parasite which threatens lamb health and sheep farming sustainability in the UK. With apparent changes in epidemiology of N. battus and the emergence of BZ-resistance in this species, [11][12][13][14] it provides an interesting case study to explore variation throughout the country. It is important to understand variation in disease observed on farm, current management practices employed and the rationale behind these control strategies to support the development of optimised control practices in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature effects (studied in laboratory) on hatching (n p = 8, n r = 18, ) (Crofton 1965; Melville et al . 2020), development (n p = 14, n r = 29, ) (Ciordia & Bizell 1963; Gyeltshen et al . 2022), and survival (n p = 15, n r = 19, ) (Gardner et al .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the nonchilling eggs changes the hatching dynamics and creates a new transmission window. On most UK farms in a recent study, the numbers of hatched eggs hav been shown to be higher with a chilling stimulus, but on some farms, independent of geographic location, non-chilling hatching is the predominant mechanism (Melville et al, 2020). Changes in the hatching patterns of N. battus are probably due to genetic adaptation to factors such as climate change, grazing management and farming practices.…”
Section: Changing Patterns Of Nematodirus Battus Infection In Sheepmentioning
confidence: 94%